Sinergi Cuci Tradisional dan Modern untuk Pelestarian Budaya dan Usaha Lokal - Suryawan, Ryan Firdiansyah; Husainah, Nazifah; Latuconsina, Abdul Samad; Pahala, Yosi; Sumardi, Sumardi (Penerbit Goodwood, 2025)
Purpose: To provide strategic recommendations for traditional and modern laundry business actors in designing service innovations, improving operational efficiency, and strengthening customer satisfaction and loyalty amid increasingly fierce business competition. Methodology/approach: This service activity employs participatory and educational methods to encourage active community involvement in developing local culture-based businesses. Results/findings: The synergy between traditional washing and modern laundry can encourage the preservation of local culture and the development of community businesses. Innovation, cross-generational collaboration, and strengthening cultural values are key to business sustainability and competitiveness in the modern era. Conclusion: The program demonstrates that blending traditional practices with modern laundry technology can enhance local businesses, preserve cultural identity, and foster community empowerment. The Pringsewu model proves that culture-based entrepreneurship is both sustainable and competitive when supported by inclusive, adaptive and collaborative approaches. Limitations: This study is limited to the Pringsewu region and does not include quantitative analysis. Contribution: This study contributes to the literature by strengthening the synergy between local culture and modern innovation as a strategy for sustainable business development and preservation of traditional values in the context of the community economy.